Creative Storytelling Through Sock Puppet Media for IGRA Teachers in North Bengkulu - Jusmadi, Evryeni; Margaretha , Lydia; Rulismi, Dwi; Sari , Zona Junita; Syakirah, Kesya (Universitas Dehasen Bengkulu, 2025)
This community service activity aims to enhance the storytelling skills of IGRA teachers through creative methods using sock hand puppets as instructional media. Conducted by lecturers from the Early Childhood Teacher Education Program (PGPAUD) of Universitas Dehasen Bengkulu, the activity took place on May 24, 2025, at the PD IGRA Secretariat in North Bengkulu and involved 50 RA teachers. The implementation included interactive lectures, demonstrations, hands-on practice, and reflective sessions. The results showed increased teacher competence in creating and utilizing sock puppets effectively. Furthermore, the activity fostered collaborative networks between the university and early childhood educators. It is recommended that similar activities be continued regularly to support the improvement of early childhood education quality.